Controlling the formation of 1D TiO2 nanowires and their performance in photoreduction of chromium Cr(VI) - Diana Vanda Wellia; Resha Mutia Rahma; Syukri Arief; Riki Subagyo; Yuly Kusumawati (Case Studies in Chemical and Environmental Engineering, 2024)
In this study, the generation of 1D TiO2 nanowires was controlled by introducing NH4OH in a one-step hydrothermal method. The increasing amount of NH4OH reduced the width of the resulting TiO2 nanowires, revealing that NH4OH altered the morphologies of the synthesized TiO2 nanowires. NTW20 showed the best photoreduction performance since NTW20 had smaller widths, large surface area and more efficient redox reaction on the surface. In comparison, the absence of photocatalyst yielded a low photoreduction activity of 5.7 %, indicating that the synthesized TiO2 nanowires showed an excellent performance in photocatalysis reactions.